Isochoric thermal conductivity of solid n-alkanes: hexane C₆H₁₄ - Konstantinov, V.A.; Revyakin, V.P.; Sagan, V.V. (Физика низких температур, 2011)
The isochoric thermal conductivity of solid n-hexane C₆H₁₄ has been investigated on three samples of different density in the temperature interval from 100 K to the onset of melting. In all the cases the isochoric thermal conductivity varied following a dependence which is weaker than Λ ∝ 1/Т. The results obtained are compared with the thermal conductivities of other representatives of n-alkanes. The contributions of low-frequency phonons and “diffuse modes” to the thermal conductivity are calculated.